Presentation of Meibomian Acini Compared to Dermal Papillae of the Eyelid Margin, Using Confocal Laser Scanning Microscopy and Corresponding Histology - Csorba, A.; Imre, L.; Szalai, I.; Lukáts, O.; Fodor, E.; Szabó, A.; Nagy, Z. Z. (Klinische Monatsblätter für Augenheilkunde, 2024)
Background Numerous studies have investigated the eyelid margin using confocal laser scanning microscopy (CLSM) and have presented morphological alterations of the examined structures, which were presumed to be Meibomian acini. However, recent data confirm that these structures are the cross-sections of dermal papillae of the dermoepidermal junction. This study aims to present the morphological appearance of Meibomian acini examined by confocal laser scanning microscopy in comparison to dermal papillae, and to reveal the corresponding patterns with specific histological sections.Methods and Material Twenty healthy patients were examined with a CLSM device in vivo at the marginal edge of the eyelid. Twenty-two samples of full-thickness eyelid wedges from 22 patients treated surgically with ectropion were collected, of which 11 freshly excised samples were imaged on the incision surface with CLSM ex vivo and 11 eyelids underwent conventional histological preparation. The represented structures on CLSM images were compared to Meibomian acini on histological sections in terms of area, longest and shortest diameter, as well as depth and density.Results On in vivo CLSM images, Meibomian orifices, epidermal cells, and dermal connective tissue could be identified, the latter in a cross-sectional view of the dermal papillae surrounded by basal cells of the epidermis, forming reflective ring-like structures. All morphological parameters of these structures differed from Meibomian acini measured on histological sections. In contrast, the CLSM images of the incision surface showed acinar units with the same morphology as the Meibomian acini seen in the histological images and no statistically significant difference was found between the corresponding parameters.Conclusion The morphological appearance of Meibomian acini differs from the structures that were previously presumed as Meibomian glands on CLSM images. In vivo imaging of Meibomian glands by commonly used in vivo CLSM cannot be performed.
Keywords: Meibomian glands; confocal laser scanning microscopy; dermal papillae; dermoepidermal junction; eyelid